Proffesional Activities as a Basic for the Proffesional Inclusion of People whit Intellectual Disabilities in the Opinion of Employers from the Wielkopolska Region - Rymaniak, Janusz; Wojciechowska, Katarzyna (Studia Oeconomica Posnaniensia, 2013)
The authors present the results of empirical research conducted among 187 organizations relating to the opinions of employers on the employment of people with intellectual disabilities. The study used Prediger's model, specifying 40 types of professional activities as possible components of work. The paper presents differences of opinions regarding work in the economy and work in the respondent's organization. It also indicates the difficulty of designing work on the basis of the activities listed and the difficulty in applying economic criteria for such jobs in the open labour market.